PENGARUH INFORMASI AKUNTANSI DAN NONAKUNTANSI TERHADAP NILAI PERUSAHAAN DI BURSA EFEK INDONESIA - Ricky; Riki Sanjaya (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to examine the effect of profitability, institutional ownership, managerial ownership, dividend policy, firm size, capital structure, liquidity ratio, and activity ratio on firm value in nonfinancial companies listed in Indonesia Stock Exchange. This research used 54 listed nonfinancial companies listed in Indonesia Stock Exchange and the data were selected using purposive sampling method, during the research period 2016 until 2018. Data were analyzed using multiple regression method. The research results show that profitability, institutional ownership, managerial ownership, firm size, capital structure, and activity ratio had significant effect towards firm value, whereas dividend policy and liquidity ratio had no effect towards firm value.